Pollination : the enduring relationship between plant and pollinator - Walker, Timothy, 1958- (Princeton University Press, 2020)
An enticing illustrated look at pollination, one of the most astonishing marvels of the natural world. Pollination is essential to the survival of most plants on Earth. Some plants rely on the wind to transport pollen from one flower to another. Others employ an array of ingenious strategies to attract and exploit pollinators, whether they be insects, birds, or mammals. This beautifully illustrated book provides an unprecedented look at the wonders of pollination biology, drawing on the latest science to explain the extraordinarily complex relationship between plant and pollinator, and revealing why pollination is vital for healthy ecosystems and a healthy planet. Timothy Walker offers an engaging introduction to pollination biology and explores the many different tactics of plant reproduction. He shows how wind and water can be effective yet wildly unpredictable means of pollination, and describes the intimate interactions of pollinating plants with bees and butterflies, beetles and birds, and lizards and bats. Walker explores how plants entice pollinators using scents, colors, and shapes, and how plants rely on rewards as well as trickery to attract animals. He sheds light on the important role of pollination in ecology, evolution, and agriculture, and discusses why habitat management, species recovery programs, and other conservation efforts are more critical now than ever. Featuring hundreds of color photos and illustrations, Pollination is suitable for undergraduate study and is an essential resource for naturalists, horticulturalists, and backyard gardeners.